Child Health Insurance Coverage and Household Activity toward Child Development in Four South American Countries - Wehby, George (2014)
OBJECTIVES: We evaluate the association between child health insurance coverage and household activities that enhance child development. METHODS: We use micro-level data on a unique sample of 2,370 children from four South American countries. Data were collected by physicians via in-person interviews with the mothers. The regression models compare insured and uninsured children seen within the same pediatric care practice for routine well-child care and adjust for several demographic and socioeconomic characteristics. We also stratify these analyses by selective household demographic and socioeconomic characteristics and by country. RESULTS: We find that insurance coverage is associated with increasingly engaging the child in development-enhancing household activity in the total sample. This association significantly varies with ethnic ancestry and is more pronounced for children of Native or African ancestry. When stratifying by country, a significant positive association is observed for Argentina, with two other countries having positive but insignificant associations. CONCLUSIONS: The results suggest that insurance coverage is associated with enhanced household activity toward child development. However, other data and research are needed to estimate the causal relationship.